THE ROLE OF SELECTED SCHOOL STAFF IN THE INCLUSIVE EDUCATION SYSTEM OF THE CZECH REPUBLIC - Smolíková, Monika; Pastieriková, Lucia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The inclusive trends of the mainstream of the education system in the Czech Republic not only affect legislative and economic changes, but the quality education platform is also determined by the arrangement of normal conditions in such a way as to create adequate space for all participating individuals. The key role of quality education in inclusive education is played by both the guidance system and the pedagogical and non-pedagogical staff of individual schools. Qualitatively Oriented Research of the Student Grant Competition of the Palacký University in Olomouc “Research of inclusion in individuals with special needs” (IGA_PdF_2019_024) builds on several years of research of the Institute of Special and Educational Studies. From the methodological point of view the qualitative design of the research was chosen. The research uses qualitative methods of data collection - in the form of semi-structured interviews. The individual data obtained from the research sample were transcribed and the data processed using the open coding technique in R Core (R Core Team, 2019). The research sample consisted of special educators, educational advisors and class teachers at the second stage of primary schools in the Czech Republic and contained interviews from 20 respondents in each category. Although the results of the research have shown the overall coherence of the system of care for individuals with special educational needs, this is largely influenced by the lack of awareness among individual school staff about the competences of all stakeholders in education. The individual settings of individual schools make it difficult to identify the general characteristics of an ideal model of collaboration between teaching staff, but despite this high variability, the core needs of all groups have been identified, which can be divided into administrative matters, mutual relations and communication.